Head and Neck Lymphoma: Clinico-demographic Profile and Pattern of Presentations in a South Western Nigeria Tertiary Institution - Adewale Adejobi; Oluwatobi Ojediran; Elijah Oyetola; Ethelbert Ugwu; Olusola Olarewaju (Nigerian Dental Association, 2024)
Abstract Running title: A clinic-demographic profile and presentation of patient with head and neck lymphoma in a tertiary institution located in low-middle-income country. Introduction Lymphoma is the second most common malignancy occurring in the head and neck region. It is broadly classified into Hodgkins lymphoma (HL) and non-Hodgkins lymphoma (NHL). It affects nodal and extra-nodal. The clinical presentation is largely determined by the anatomic distribution of the disease, clinical stage of the disease, age of the patients and presence of underlying diseases. Aims and Objectives This study aims to analyse the presentation of head and neck lymphomas over a fifteen years period at Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife. The objectives include; to determine the prevalence and demographic indices (age and gender) of head and neck, document the histopathologic types, and determine the association between the anatomical sites and histopathologic subtypes of lymphomas Materials and Method This is a retrospective study among patients seen and diagnosed histologically with head and neck lymphomas between 2005 - 2019 at the departments of Oral Medicine and Pathology and Morbid Anatomy and Forensic Medicine, OAUTHC. Relevant record were retrieve from patient record and histological register from the hospital registry. Patients with incomplete data were excluded. The study was conducted in accordance with the Declaration of Helsinki, and approved by our institution Ethics Committee Board. Results A total number of 54 cases of head and neck lymphoma were analysed with a prevalence of 30.9%. Out of the 54 cases, 46 were NHL and 8 cases were HL with a ratio of 5.8:1 respectively. A male preponderance was observed (M: F; 2.4:1). The lesion commonly affects patients in 3rd and 4th decade of life. All the histologic variants were seen to affect males more than females except for the unclassified variant of HL which affected both sexes equally. Low-grade and intermediate grade NHL affected the older patients more while high grade and miscellaneous subtypes affected the younger males. The cervical lymph nodes were the most common nodal site while the jaw was the most common extra-nodal site. Eighteen (39.1%) cases of NHL were diagnosed histological as miscellaneous while high and low grade had seven (15.2%) cases each. Conclusion Head and neck lymphoma remain relatively rare. One of every six lymphoma seen was HL, with male preponderance. High grade lymphoma is seen more in the younger patient. Lymphoma affect cervical lymph node more while jaw was the most common extranodal site. Obesity may be a predisposing factor in our environment but require future study to confirm.